2017
DOI: 10.1158/1055-9965.epi-16-0595
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection and Survival of Lymphoma Patients in the Era of Highly Active Antiretroviral Therapy

Abstract: Background: Highly active antiretroviral therapy

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 38 publications
5
40
1
4
Order By: Relevance
“…Treatment outcomes for patients with HIV-related lymphoma have improved in the era of effective antiretroviral therapy (ART), in particular for DLBCL and Burkitt lymphoma, and curability of HIVrelated lymphoma is considered similar to that of HIV-unrelated lymphoma 8. However, we found that patients with HIV-related DLBCL had worse survival, consistent with a recent US study 9. A previous study conducted by the Eastern Cooperative Oncology Group showed that rituximab plus chemotherapy is very effective to treat HIV-associated B-cell NHL among patients aged ≥18 years, and no increase of infection-related deaths was observed 10.…”
supporting
confidence: 89%
“…Treatment outcomes for patients with HIV-related lymphoma have improved in the era of effective antiretroviral therapy (ART), in particular for DLBCL and Burkitt lymphoma, and curability of HIVrelated lymphoma is considered similar to that of HIV-unrelated lymphoma 8. However, we found that patients with HIV-related DLBCL had worse survival, consistent with a recent US study 9. A previous study conducted by the Eastern Cooperative Oncology Group showed that rituximab plus chemotherapy is very effective to treat HIV-associated B-cell NHL among patients aged ≥18 years, and no increase of infection-related deaths was observed 10.…”
supporting
confidence: 89%
“…197 One large database study, however, found that overall survival was decreased in PLWH and HL (hazard ratio [HR], 1.47; 95% CI, 1.25-1.74), even though the population was matched by treatment characteristics. 198 Cancer-specific survival was not assessed in this study.…”
Section: Management Of Hl In Plwhmentioning
confidence: 99%
“…The incidence of cHL in the HIV setting have increased 5-25-fold, suggesting that despite suppressive cART, the ongoing immune suppression (driven by ongoing HIV replication among other factors) and the aged population have contributed to this rise [7][8][9][10][11][12][13]. On the other hand, individuals with severe immune suppression have a lower cHL incidence, suggesting that the improvement of CD4 counts associated to cART and the rise of immune competence may explain the observed increase of cHL incidence [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%